Treści z zakresu ochrony przyrody w edukacji leśnej społeczeństwa - Referowska-Chodak, Ewa (Leśne Prace Badawcze, 2012)
The State Forests – National Forest Holding protects, utilizes and shapes Poland’s public forests over an area exceeding 7.5 million hectares. Apart from these tasks, it undertakes the forestry education of the society. Today, about 1.5-2 million people benefit every year from the educational activities offered by the State Forests. These are mainly financed by the State Forests organisational units’ themselves. Nature protection is an essential aspect of the society’s forestry education. It should include both information about traditional values of nature protection and up to date ecological forest management. Existing references offer detailed information designed for groups of various ages who benefit from such an education. The provision of information about nature protection in forests highlights a number of challenges that have to be met, e.g. stereotypes in social awareness, unavoidable involvement of both foresters and teachers/counsellors, the tendency to concentrate on particular questions while discounting other ones, etc. The widely understood fundamentals of nature protection should be an important component of forestry education, because they can reduce the number of conflicts resulting from an insufficient social awareness of the aims, rules and methods of nature conservation in forests.